MiR-146a-5p Mimic Inhibits NLRP3 Inflammasome Downstream Inflammatory Factors and CLIC4 in Neonatal Necrotizing Enterocolitis - Chen, Jianglong; Chen, Tong; Zhou, Jin; Zhao, Xiuhao; Sheng, Qingfeng; Lv, Zhibao (Frontiers in Cell and Developmental Biology, 2021)
Objective: Necrotizing enterocolitis (NEC) is a gastrointestinal emergency with a severe inflammation storm, intestinal necrosis, and perforation. MicroRNA-146a-5p (miR-146a-5p) has been reported to be a valuable anti-inflammatory factor in various intestinal inflammatory disorders. However, the role of miR-146a-5p in NEC, its effects on nucleotide-binding domain and leucine-rich repeat-containing protein 3 (NLRP3) inflammasome, and its downstream inflammatory factors remain unknown. This study aimed to investigate the role of miR-146a-5p and NLRP3 inflammasome and its downstream inflammatory factors in NEC development. Methods: The expression levels of miR-146a and NLRP3 inflammasome were investigated in intestinal tissues. Next, the mechanism by which miR-146a-5p regulates NLRP3 inflammasome activation was explored in vitro in THP-1 cells. Finally, to identify the effects of miR-146a-5p on NEC in vivo, NEC mice were transinfected with miR-146a-5p overexpression adenovirus before the occurrence of NEC. Results: NLRP3 inflammasome enzymatic protein caspase-1 and its downstream inflammatory factors increased in NEC intestinal samples in both humans and mice, and miR-146a-5p expression level was increased and mainly expressed in the macrophages of the affected intestine. In vitro, only miR-146a-5p mimic inhibited NLRP3 inflammasome downstream inflammatory factors and its upstream protein chloride intracellular channel protein 4 (CLIC4) expression in cellular membrane in the THP-1 cell line, and this only occurred under mild/moderate LPS concentration. MiR-146a-5p overexpression adenovirus transfection reduced CLIC4 cellular membrane expression and inhibited NLRP3 downstream factors increasing in vivo. After the transfection of miR-146a-5p adenovirus, the survival rate of NEC mice was increased, and intestinal injury was ameliorated. Conclusion: MiR-146a-5p inhibited NLRP3 inflammasome downstream inflammatory factors and CLIC4 membrane expression in NEC. Additionally, miR-146a-5p could attenuate inflammation and intestinal injury in the NEC-affected intestine.